Reviewing the literature on working dual jobs among workers with specific discussion on Malaysian women - Mohd Afsur Khan, Aslynda Jane; Abd. Rokis, Rohaiza (IIUM Press, International Islamic University Malaysia, 2020)
Quite recently, working dual jobs among workers in Malaysia was permitted by the government on the grounds of earning additional income as a substructure for daily living, managing household debts and soldiering on towards achieving a sustainable future. The Malaysian Central Bank’s report indicated that ‘gaji kehidupan wajar’ or the living wage is needed for a household to afford a minimum acceptable living standard as well as a substance for a developing nation. Concurrently, the living wage also was seen to be a potential tool in reviewing current salaries relevancies for Malaysian employees. Assuming that the national living wage is yet attainable, working dual jobs were allowed to certain working sectors. However, the permission was bound to a specific act and circular since it only involved primary official jobs. Working dual jobs can be one of the initiatives to supplement everyday living for most families. This article selects 10-year official-based and academic-content literature that review the relevant concepts of working dual jobs from both international and Malaysian situations. The compilation of this contemporary reviewed reading materials may be useful for the academics and researchers to undertake further deliberation in this pressing socio-financial situation among Malaysian workers, particularly women. As further, this compilation of study may have significance towards the organisational context in the prevalence of women’s empowerment and work-life balance today.